2020
DOI: 10.1186/s12954-020-00432-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on harm reduction services in Spain

Abstract: Background Containment policies and other restrictions introduced by the Spanish government in response to the COVID-19 pandemic present challenges for marginalised populations, such as people who use drugs. Harm reduction centres are often linked to social services, mental health services, and infectious disease testing, in addition to tools and services that help to reduce the harms associated with injecting drugs. This study aimed to explore the impact of the pandemic on these services in four autonomous co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
(19 reference statements)
2
36
0
1
Order By: Relevance
“…Globally, this has included changes to drugs harm reduction services, including: designating harm reduction services to be essential [ 46 ]; developing emergency harm reduction plans [ 46 ]; access to COVID-19 screening and testing [ 47 ]; changes to service and medication provision to comply with pandemic guidance [ 41 , 42 , 46 – 56 ]; improved access to naloxone and IEP [ 47 , 50 ]; increased awareness of the need for clean water for injecting [ 57 ]; general guidance about reducing COVID-19 spread in services [ 58 – 60 ]; the need for a ‘safe supply’ of drugs [ 46 ]; and the need for holistic models of care that attend to mental and physical health and housing needs [ 46 ]. While evidence is still emerging on how the pandemic impacted drugs harm reduction, strict lockdown rules have appeared to reduce the number of people accessing IEP and other harm reduction services [ 61 , 62 ]. Other public health guidelines, such as social distancing, maintaining high levels of personal hygiene including regular hand washing and the wearing of masks, place additional demands on people who use substances, which may hinder the provision of effective services [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, this has included changes to drugs harm reduction services, including: designating harm reduction services to be essential [ 46 ]; developing emergency harm reduction plans [ 46 ]; access to COVID-19 screening and testing [ 47 ]; changes to service and medication provision to comply with pandemic guidance [ 41 , 42 , 46 – 56 ]; improved access to naloxone and IEP [ 47 , 50 ]; increased awareness of the need for clean water for injecting [ 57 ]; general guidance about reducing COVID-19 spread in services [ 58 – 60 ]; the need for a ‘safe supply’ of drugs [ 46 ]; and the need for holistic models of care that attend to mental and physical health and housing needs [ 46 ]. While evidence is still emerging on how the pandemic impacted drugs harm reduction, strict lockdown rules have appeared to reduce the number of people accessing IEP and other harm reduction services [ 61 , 62 ]. Other public health guidelines, such as social distancing, maintaining high levels of personal hygiene including regular hand washing and the wearing of masks, place additional demands on people who use substances, which may hinder the provision of effective services [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first wave from March to June prompted a country-wide lockdown and the second wave has been ongoing since September. During this overall period, there has been a drop in HCV testing, linkage to care, harm reduction programs, and microelimination programs 3 . We aimed to assess the impact of COVID-19 on hepatitis C elimination in Spain.…”
mentioning
confidence: 99%
“…Also, a study examining the COVID-19 effects on NEP in England showed that the number of clients and number of visits decreased by 36% and the number of needles distributed decreased by 29% [ 4 ]. Furthermore, a study from Spain reported a 22% decrease in service users across all studied harm reduction centres and a 40% decrease in average needle distribution as well as a reduction in in HIV/hepatitis testing [ 4 , 20 ].…”
Section: Discussionmentioning
confidence: 99%